Analisis Pelaksanaan Take Over Pembiayaan Nasabah Pensiunan - Anri, Anri (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the implementation of take over financing for retired customers to know how to implement the Take Over financing for retired customers at PT. Indonesian Islamic Bank KCP Abdulah bin Nuh Cianjur. This type of research uses descriptive qualitative with data collection techniques using participatory observation methods, interviews, documentation studies, triangulation, secondary data, and primary data. Based on the results of the discussion it can be concluded that the implementation of retirement take over financing is the submission of customers, requests for take over, approval of take over, disbursement of requests and contracts, collateral collection, and monitoring..